Properties of palm oil fuel ash cement based aerated concrete [electronic resource] - Khairunisa Mutusamy, 1978-; Fakulti Kejuruteraan Awam (2009)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2009